2003
DOI: 10.1073/pnas.1130145100
|View full text |Cite
|
Sign up to set email alerts
|

Exponential growth by cross-catalytic cleavage of deoxyribozymogens

Abstract: We have designed an autocatalytic cycle based on the highly efficient 10 -23 RNA-cleaving deoxyribozyme that is capable of exponential amplification of catalysis. In this system, complementary 10 -23 variants were inactivated by circularization, creating deoxyribozymogens. Upon linearization, the enzymes can act on their complements, creating a cascade in which linearized species accumulate exponentially. Seeding the system with a pool of linear catalysts resulted not only in amplification of function but in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 36 publications
0
54
0
Order By: Relevance
“…Other scientists have proposed that life might have originated with a set of molecules whose cross-catalytic activity would produce an autocatalytic cycle [FKP86,Wäc88,Wäc90]. While mathematical analysis of models of these systems has suggested that they have the ability to evolve [Eig71, Kau93, SBEL00], experimental demonstrations have been restricted to either systems for which catalysis does not form a complete cycle [HW], or to systems that contain autocatalytic cycles that do not obviously appear capable of non-trivial evolution [vK86,LGMKSa96,LE03]. The most well-accepted hypothesis about life that preceded the current DNA/RNA/protein life is the RNA world hypothesis, which proposes that genetic information was once stored by RNA molecules which could catalyze their own replication.…”
Section: Introductionmentioning
confidence: 99%
“…Other scientists have proposed that life might have originated with a set of molecules whose cross-catalytic activity would produce an autocatalytic cycle [FKP86,Wäc88,Wäc90]. While mathematical analysis of models of these systems has suggested that they have the ability to evolve [Eig71, Kau93, SBEL00], experimental demonstrations have been restricted to either systems for which catalysis does not form a complete cycle [HW], or to systems that contain autocatalytic cycles that do not obviously appear capable of non-trivial evolution [vK86,LGMKSa96,LE03]. The most well-accepted hypothesis about life that preceded the current DNA/RNA/protein life is the RNA world hypothesis, which proposes that genetic information was once stored by RNA molecules which could catalyze their own replication.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the entire network could be viewed as an "individual", in which specific sequences are required for collaboration to produce an autocatalytic network. This system provides an example of predicted missing links [9] between the first self-replicating nucleic acid templates and a more complex RNA world, in line with Eigens demarcation. Future work will examine whether collaborating molecules can display a selective advantage through autocatalysis and if a mutated population derived from these sequences can evolve over time.…”
mentioning
confidence: 82%
“…Implementations are found in two recent schemes involving hybridization networks. [7,8] Genetic autocatalysis is usually attributed to self-replication (the autocatalytic transfer of information from templates to copies), and examples based on nucleic acids, [9][10][11][12][13][14] peptides, [15,16] and organic molecules [17] as templates have been studied. This approach was greatly influenced by Eigens description of the self-organization of matter that requires autocatalysis to evolve from a prebiotic "chemical" phase to a self-organization of replicating "individuals" phase, which must have occurred contemporaneously.…”
mentioning
confidence: 99%
“…Although in principle ribozymes and deoxyribozymes could participate in similar cascades as catalysts [10][11][12], no generalizable method for implementing such cascades has yet been established. On the other hand, DNA and RNA can catalyze chemical reactions not only by forming intricate tertiary structures, but also by simply forming Watson-Crick base pairs.…”
Section: Resultsmentioning
confidence: 99%